What Factors Moderate Self-Other Discrepancies in Decision Making? Results from a Vaccination Scenario. (20th September 2016) - Petrova, Dafina; Garcia-Retamero, Rocio; van der Pligt, Joop
Abstract: When we make risky decisions for others, we tend to follow social norms about risks. This often results in making different decisions for others than we would make for ourselves in a similar situation (i.e., self-other discrepancies). In an experiment, we investigated self-other discrepancies in young adults' decisions to purchase a vaccine against a sexually-transmitted virus for themselves or for another person (i.e., the target of the decision). When the target's preferences were in line with social norms, surrogates showed large self-other discrepancies in line with these norms. When the target's preferences were contrary to social norms, surrogates did not show self-other discrepancies in line with these preferences; instead they still followed social norms, F (1, 140) = 21.45, p < .001, η p 2 = .13. Surrogates with lower numeracy, F (2, 128) = 3.44, p = .035, η p 2 = .05, and higher empathy, F (2, 128) = 3.72, p = .027, η p 2 = .06, showed self-other discrepancies more in line with the target's preferences, even when these were contrary to the norm. Surrogates whose own risk attitudes were contrary to social norms showed larger self-other discrepancies, F (1, 128) = 5.38, p = .022, η p 2 = .04. These results demonstrate that perceived social norms about risk can predict self-other discrepancies in risky decisions, even when the target's preferences are known and at odds with the social norm. Further, the surrogates' numeracy, empathy, and propensity to take risks influence the extent to which risky decisions for others resemble risky decisions for oneself.